Solid Modeling and Applications Rapid Prototyping, CAD and CAE Theory - Um, Dugan (Springer International Publishing, 2018)
This updated, second edition provides readers with an expanded treatment of the FEM as well as new information on recent trends in rapid prototyping technology. The new edition features more descriptions, exercises, and questions within each chapter. In addition, more in-depth surface theory has been introduced in section four, with particular emphasis in surface theory. Promising cutting edge technologies in the area of rapid prototyping are introduced in section seven, MATLAB-based FEM analysis has been added in section eight, and development of the plan stress and plane strain stiffness equations are introduced as a new chapter. Revised and updated based on student feedback, Solid Modeling and Applications: Rapid Prototyping, CAD and CAE Theory is ideal for university students in various engineering disciplines as well as design engineers involved in product design, analysis, and validation. It equips them with an understanding of the theory and essentials and also with practical skills needed to apply this understanding in real world design and manufacturing settings. New edition expands sections on rapid prototyping, surface theory, plan stress and plane strain stiffness equations, and MATLAB-based FEM analysis; Introduces the theory and application of CAD, CAE, and rapid prototyping to students of mechanical or manufacturing engineers with little or no coding experience; Maximizes student capability applying theory-based solutions to practical problems; Increases students' insight into concepts of each theory using mathematical problems; Reinforces student understanding of CAD/CAE theory with numerous examples and exercises throughout the book; Includes precoded spreadsheet exercises.